use of data and information to support the development of public policies in the State of Alagoas: a case study at the Superintendence of Information and Scenarios (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The Brazilian State, according to the 1988 Constitution, aims to promote the public interest, where data and information are crucial for shaping public policies. In this regard, Information and Communication Technologies assist public administration, making it more responsive to demands. This study is a case study at the Superintendence of Information and Scenarios, involving a participative approach, exploratory analysis, qualitative research, bibliographic and documentary studies, including workflow mapping, information cycle, and technology assessment. Results include improvements in work processes and some public policies benefited by efficient information provision.
Keywords: information; public policies; Alagoan society; data-driven government